2021
DOI: 10.1016/j.ijid.2021.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Screening of SARS-CoV-2 among homeless people, asylum-seekers and other people living in precarious conditions in Marseille, France, March–April 2020

Abstract: Background Surveillance of SARS-CoV-2 infection among sheltered homeless and other vulnerable people might provide the information needed to prevent its spread within accommodation centres. Methods Data was obtained from 698 participants in different accommodation centres (411 homeless individuals, 77 asylum-seekers, 58 other persons living in precarious conditions, and 152 employees working in these accommodation centres) who completed questionnaires and had nasal samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 20 publications
4
64
2
Order By: Relevance
“…A wide variety of studies sustain the idea that crowded household settings constitute an important site for COVID-19 outbreaks (19,(21)(22)(23)(24)(25)(26). Our study shows that 9 of 11 of the shelters had active COVID-19 outbreaks confirming that this kind of facilities are of high risk for SARS-CoV-2 transmission.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A wide variety of studies sustain the idea that crowded household settings constitute an important site for COVID-19 outbreaks (19,(21)(22)(23)(24)(25)(26). Our study shows that 9 of 11 of the shelters had active COVID-19 outbreaks confirming that this kind of facilities are of high risk for SARS-CoV-2 transmission.…”
Section: Discussionsupporting
confidence: 72%
“…The same study recommended resident stability J o u r n a l P r e -p r o o f to reduce COVID-19 cases (25). Nevertheless, another study carried out at shelters in France also suggest the risk of collective housing for SARS-CoV-2 transmission and found a SARS-CoV-2 attack rate of 7% (26). Interestingly, we described how the occupation of some shelters included in our study reached or even surpassed the shelter capacity according to data provided by UNHCR; considering that we found COVID-19 outbreaks at most of the shelters, recurrent screening for SARS-CoV-2 infection should be implemented.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that the most strongly associated seropositivity risk factors were those linked to crowded living conditions. A French survey revealed the role of collective housing in relation to viral transmission within accommodation centers [ 15 ] Another French study identified that overcrowding is the most important factor explaining variability in exposure, rather than reported adherence to recommended preventive measures [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 quantitative studies were conducted in the USA [23À41], three in Canada [42À44],three in France [16,45,46], two in Italy [47,48], and one in Belgium [49], Spain [50], Slovakia [51], and Denmark [52], respectively. The data collection period considering all studies ranged from January 2020 to October 2020.…”
Section: Resultsmentioning
confidence: 99%
“…the proportion of infected individuals after which an outbreak is unlikely to go extinct without an external intervention or before infecting the full population [15]. As these thresholds are based on previous data, we chose the lowest reported prevalence measure (9% [16]) and decided on rounding down to an even lower threshold of 5% to be conservative. Further, risk of bias and publication bias were assessed through funnel plots and regression-based statistical testing by Egger et al [17,18].…”
Section: Discussionmentioning
confidence: 99%